A Seat at the Table: Exploring 4.0 Leadership Attributes Using a Thematic Approach - Daud S.; Hanafi W.N.W. (Springer Science and Business Media B.V., 2023)
As we are transforming towards the fourth industrial revolution, in the era of technological change and competitive world, organizations need to employ a leadership style that could help the organization to survive. Fourth industrial revolution leadership is defined by the ability to rapidly align, engage, and empower networked teams with clarity of purpose and powerful resolution to win. The objectives of the study are to capture the indicators that will assist in confirming the indicators for the 4.0 leadership in the manufacturing industry in Malaysia. The data collection for this study includes a preliminary observation of company practices, focus group discussions, in-depth interview, and an expert opinion interview. Fifteen themes emerged from the data; idealized influences, inspirational motivation, innovative, visionary, courage, passion, strategic thinking, focus, collaborative, flexible, communication, accountable, tech savvy, entrepreneurial, and agile. There is no doubt that Malaysias manufacturing industry is under pressure to maintain organizational effectiveness and efficiency. The emphasis on human capital and productivity is critical for going forward and remaining competitive in such a challenging environment. Thus, the findings from this study could provide insights on leadership attributes that leaders could use to sustain their operations for the longer term in the fourth industrial revolution. 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.